1976
DOI: 10.1037/h0077211
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of behavioral arousal in rats: Effect of maternal and sibling presence.

Abstract: Spontaneous locomotor activity of 5-to 30-day-old rats housed either alone or in the presence of various components of the normal nest and litter stimuli was recorded by means of time-lapse videography. Developing animals observed alone showed a sharp increase in total daily locomotor activity from Day 5 to Day 15 followed by a rapid decline from Day 15 to Day 30. Individual animals observed in the context of the normal litter environment showed an entirely different pattern of development. They were relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 18 publications
6
41
1
Order By: Relevance
“…Preliminary testing indicated that 15-day-old pups exhibited high levels of activity when isolated from littermates in a novel context, and this activity did not habituate during the 7-min test. This hyperactivity was inconsistent with what had been observed in Experiment 1; however, it was consistent with studies showing a peak in isolation-induced locomotion at this age (Campbell & Raskin, 1978;Randall & Campbell, 1976). These published reports also determined that the locomotion was induced by separation from home-nest cues and did not occur in the presence of the mother, littermates, or other home-nest stimuli (Campbell & Raskin, 1978).…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Preliminary testing indicated that 15-day-old pups exhibited high levels of activity when isolated from littermates in a novel context, and this activity did not habituate during the 7-min test. This hyperactivity was inconsistent with what had been observed in Experiment 1; however, it was consistent with studies showing a peak in isolation-induced locomotion at this age (Campbell & Raskin, 1978;Randall & Campbell, 1976). These published reports also determined that the locomotion was induced by separation from home-nest cues and did not occur in the presence of the mother, littermates, or other home-nest stimuli (Campbell & Raskin, 1978).…”
Section: Methodssupporting
confidence: 82%
“…Reports in adult rats also indicated that familiar conspecifics facilitate exploration of an open field (Hughes, 1969). On the other hand, infant rats show a strong motive to huddle together during the preweanling period, resulting in a suppression of activity (Randall & Campbell, 1976); thus, it might be predicted that the presence of littermates at these ages would inhibit exploration.…”
Section: Introductionmentioning
confidence: 96%
“…Possibly, much of this accentuated behavior may be the product of matcrrial and sibling isolation. As noted by Randall and Campbell (1976), providing 1 5-day-olds with conspecifics markedly reduces their activity levels, and an overall smooth development of activity is noted under these conditions. Whether ultradian rhythmicity is affected by this type of manipulation remains t o be determined.…”
Section: Discussionmentioning
confidence: 88%
“…Whether this early peak level of activit y reflects differential maturation of excitatory and inhibitory neurotransmitter system s (Campbell, Lytle, & Fibiger, 1969 ; Nagy et aI., 19 75) or a response to isolati on-indu ced fear (Campbell & Raskin ,197 comp arisons conducted with in this int eraction indicated nonsignificant differen ces amon g the age groups durin g the first trial block , with the exception of th e 13-day-old group , which made more successful avoidances than all other ages [Fs(l ,432) [F(l ,432= 19.43, p< .0005] ; the 11-and 15-day-olds showed litt le change. Randall & Campbell, 1976) is unclear at this time. However, it is quite likely that this age-related change in spontaneous activity results in the higher number of active avoidance responses made by 13-day-old mice as compared with 11-and l Svday-old mice in the present study.…”
Section: Methods Proceduresmentioning
confidence: 85%